Social Identity as a Tool of Sustainable Public Deliberation - Csiszer, Annamaria (Technium Social Sciences Journal, 2020)
Social consultation in general, and communication in particular is an important form of information exchange between the public and government. The use of the 2014-2020 development funds is a crucial question in nowadays social dialogue in Hungary which is worth an analysis in order to get information about interaction between representatives and represented. In most cases the communication between the government and its citizens is a one-way communication, online and offline consultations provide space for inclusive public deliberation. My paper focuses on development policy communication, its effectiveness, its quality and its results. I am especially interested in the mental process that occurs in the head of the team, responsible for the creation of the social consultation and between the beneficiaries (citizens and professional organizations) who are targets and objects of social consultations. I build the theoretical part of my work around the phenomena of identity both from social and psychological perspectives. Backing up my conceptualization with a qualitative interview survey carried out among the participarts of the social dialogue – being either representatives of the government or citizens of the country. Finally, drawing a conclusion of the lessons of a public consultation.